(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Cardiopulmonary resuscitation (CPR) represents a critical life-saving skill that nursing students must master to respond effectively to cardiac emergencies. Understanding nursing students’ knowledge, attitudes, and perceptions regarding CPR is essential for curriculum development and ensuring competent emergency response capabilities. Objectives: This study aimed to assess the knowledge, attitudes, and perceptions regarding CPR among bachelor nursing students at the College of Nursing, Sir CJ Institute of Psychiatry, Hyderabad. Methods: A cross-sectional study was conducted among 118 undergraduate nursing students (2nd to 4th year) using convenience sampling. Data were collected using a self-administered questionnaire adapted from validated instruments, with multilingual support provided in Sindhi and Urdu languages. Results: The study participants had a mean age of 21.30±3.283 years, with male predominance (70.3%). Nearly half (48.3%) lacked CPR certification, while 60.2% had attended first aid courses. Knowledge assessment revealed significant gaps: only 2.5% correctly identified scene safety as the first response step, while 64.4% knew proper chest compression depth. Understanding of CPR acronym CAB showed equal split between correct (45.8%) and incorrect (45.8%) responses. Compression rate knowledge was moderate (42.4% correct), while rescue breathing understanding was strong (74.6% correct). Legal protection knowledge was poor, with only 31.4% correctly identifying Good Samaritan Law. Despite knowledge gaps, 75.4% had received formal CPR training, and willingness to provide CPR increased from 74.6% pre-training to 89.0% post-training. Overwhelming support (94.9%) existed for mandatory CPR training among college teachers. Conclusion: While nursing students demonstrated moderate knowledge in some CPR domains, significant gaps exist in critical areas such as scene safety assessment and legal protections. The high willingness to learn and provide CPR, combined with identified knowledge deficits, underscores the need for enhanced, structured CPR education programs in nursing curricula to ensure competent emergency response capabilities.